On a Mixed Sum-Difference Equation of Volterra-Fredholm Type - Pachpatte, B. G. (Sarajevo Journal of Mathematics, 2024)
The main objective of this paper is to study some basic properties of solutions of a mixed sum-difference equation of Volterra-Fredholm type. A variant of a certain finite difference inequality with explicit estimate is obtained and used to establish the results. 2000 Mathematics Subject Classification. 34K10, 35K10, 35K10